2009
DOI: 10.1137/080719571
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Truncated SPIKE Algorithm

Abstract: Abstract. The truncated SPIKE algorithm is a parallel solver for linear systems which are banded and strictly diagonally dominant by rows. There are machines for which the current implementation of the algorithm is faster and scales better than the corresponding solver in ScaLAPACK (PDDBTRF/PDDBTRS). In this paper we prove that the SPIKE matrix is strictly diagonally dominant by rows with a degree no less than the original matrix. We establish tight upper bounds on the decay rate of the spikes as well as the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…The existence and uniqueness of the matrix K q is immediate. Moreover, Corollary 3.2 [6] implies that…”
Section: The Main Resultsmentioning
confidence: 99%
“…The existence and uniqueness of the matrix K q is immediate. Moreover, Corollary 3.2 [6] implies that…”
Section: The Main Resultsmentioning
confidence: 99%
“…Let T denote the main block diagonal of R, see Figure 4. Mikkelsen and Manguoglu [5] showed that T − R ∞ ≤ q when A is banded and strictly diagonally dominant by rows. In this paper we consider the significance of the off diagonal blocks relative to the main block diagonal.…”
Section: Now Consider the Solution Of A Block Tridiagonal Linear Systemmentioning
confidence: 99%
“…For such systems, since spikes decay as one moves away from the main diagonal, a truncated variation of the algorithm is used. An extensive error analysis for the Truncated Spike algorithm is given in [29].…”
Section: The Spike Linear System Solvermentioning
confidence: 99%
“…Motivated by need for extreme scalability and the deep memory hierarchies of current platforms, we have developed the next generation of hybrid solversthe Spike family of algorithms [3,5,10,22,[29][30][31][32]. The Spike solver toolkit is specifically designed for banded systems (potentially sparse within the band).…”
Section: Introductionmentioning
confidence: 99%